An EFL Student case study on Content Based English Teaching –TEFL program portfolio - Miño Andrade, María Lorena (2012)
This thesis describes Content-based instruction as a useful approach to language instruction that focuses on teaching English language at the same time as teaching subject matter classes. The purpose of this study was to determine the benefits and the drawbacks of Content-based instruction as well as the different types of Content-based instruction in order to integrate better the reading, writing, listening, and speaking English language skills required for academic success. This paper also demonstrates the application of NCATE/TESOL teacher education standards in this master´s program as a way to train English teachers to provide students with quality instruction.